What makes syntactic processing of subject–verb agreement complex? The effects of distance and additional agreement features. (March 2017) - Rispens, Judith; de Amesti, Vicente Soto
Abstract: This study investigates two types of factors potentially affecting the level of complexity of processing subject–verb agreement: (i) distance between the subject and the critical verb (0, 1 or 2 constituents) and (ii) type of intervening constituent between the subject and the verb (adverb versus an NP within a PP). NPs, but not adverbs, include additional number features that potentially increase complexity of processing the agreement relationship between the number features of the subject NP and the verb. Event-related potentials (ERPs) were measured to investigate the neural correlates of agreement processing. Eighteen native Spanish speaking participants read grammatical sentences as well as ungrammatical sentences violating subject–verb agreement. The ungrammatical sentences elicited posterior negativities in the 350–500 ms time window. No effects of distance or type of constituents were found in this time window. A typical P600 effect was also observed in response to the agreement violations. The linear distance between the subject and the verb influenced the P600 effect; the sentences containing two constituents elicited more positive going waveforms compared to sentences without intervening constituents. The type of constituent did not play a role. The results fit psycholinguistic accounts assuming that integration of additional linguistic elements makes it more complex to process the subject–verb agreement relationship at the verb, regardless of the presence of additional number features. Highlights: Linear distance influences processing the dependency relationship between subject and verb. Adjacent subjects and verbs are perceived more accurately than non-adjacent ones. ERPs show that detecting subject–verb agreement violations is not affected by distance. ERPs show that reanalyzing subject–verb agreement relations is affected by distance.